2019
DOI: 10.1051/matecconf/201925405001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geometrical parameters of the forming channel on the boundary value of the axial force in the agglomeration process of dry ice

Abstract: The article presents the results of study on the influence of geometrical parameters of the forming channels on axial force which is the main parameter of the agglomeration process of dry ice in the piston method. During research, the material was agglomerated utilizing different dies. The material is characterized by low temperature and sublimation under standard environmental conditions. The study focuses on determining the influence of geometrical parameters of the conical and cylindrical sections of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For a spherical, convex, or concave convergent section, specify the radius value (R 1 or R 2 ) and the section's length (h 1 or h 2 ). In the case of the fourth type of channel, fixed from the connection of the two previous ones, it is necessary to determine the parameters for both sections independently or to ascertain the total length of the convergent section and define the proportion of each share, e.g., (CS), (d) with a convex section followed by concave section (CCS) [13] 1 to 1. The convex spherical compression section was left out based on the results of earlier studies that revealed problems with obtaining laminar flow of the material during extrusion and maintaining cohesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a spherical, convex, or concave convergent section, specify the radius value (R 1 or R 2 ) and the section's length (h 1 or h 2 ). In the case of the fourth type of channel, fixed from the connection of the two previous ones, it is necessary to determine the parameters for both sections independently or to ascertain the total length of the convergent section and define the proportion of each share, e.g., (CS), (d) with a convex section followed by concave section (CCS) [13] 1 to 1. The convex spherical compression section was left out based on the results of earlier studies that revealed problems with obtaining laminar flow of the material during extrusion and maintaining cohesion.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4. Shapes of the dies under analysis: (a) conical-cylindrical (CC), (b) with a convex spherical compression section, (c) with a concave spherical compression section(CS), (d) with a convex section followed by concave section (CCS)[13] …”
mentioning
confidence: 99%
“…It is used, among others, for food storage, water carbonization and freeze-drying of products [9,12,29]. Dry ice is also widely employed in abrasion cleaning of surfaces [15,30,40]. An important parameter defining compacted dry ice quality is its density.…”
Section: Introductionmentioning
confidence: 99%
“…If pellets of smaller dimensions are required, they are run through a strainer. Dry ice is produced in a separate system [6], i.e., using the process described in [7] or on site [8] by conversion of liquid CO 2 to pellets with the use of a pelletizer. Once the pellets are loaded in the two-phase dry ice blasting machine, compressed air blasts them through a nozzle on to the cleaning surface [9].…”
mentioning
confidence: 99%